Competência contextual e processo de legendação de filmes - Reis, Mariza de Fátima (2008)
This work is the result of a research about text translation theories established by linguistics and pragmatics, which charge the translator the reach of the original meaning even at a different time of its original context. The meaning is related to the translator process as a result of the perception he has about the extra-linguistics signs out of its authorship context. Once the study about this distance in time has no theoretical bases in pragmatic linguistic, it still demands the translator the ability to contextualize the original. To investigate the matters about free and literal translation procedures it was adopted sign, communication and contextualization linguistic concepts developed by Saussure, Jakobson and Parret respectively. The issues about the discussion between knowledgement theory and meaning validation related to the Linguistic Turn in Language philosophy , are based on speech acts concept developed by Ordinary language philosophy (Austin) under the perspective of language games developed by Wittgenstein (Investigations). Finally the practice and theory are investigated through Percian semiotic approach, re-read by Santaella and Colapietro on the matter of sign perception. They are applied in subtitling products of a scene in Forrest Gump translated both in Brazil and in Portugal. As a result it comes a new concept of literalism to the original meaning as long as the perception of the translator privileges the extra-linguistic signs that follow the audiovisual in real time, approach that facilitates the audience reception of the translation. Allowing the addition of contextual competence concept to the critical models of translation studies, the nature of this cognition suggest the existence of a contextual logic that may be added to the structural, consensual and inferencial logics already established in communicative researches